2012
DOI: 10.1007/s00277-012-1564-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of congenital sideroblastic anemia: comparison with myelodysplastic syndrome with ring sideroblast (MDS-RS)

Abstract: Sideroblastic anemia is characterized by anemia with the emergence of ring sideroblasts in the bone marrow. There are two forms of sideroblastic anemia, i.e., congenital sideroblastic anemia (CSA) and acquired sideroblastic anemia. In order to clarify the pathophysiology of sideroblastic anemia, a nationwide survey consisting of clinical and molecular genetic analysis was performed in Japan. As of January 31, 2012, data of 137 cases of sideroblastic anemia, including 72 cases of myelodysplastic syndrome (MDS)–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
0
30
1
1
Order By: Relevance
“…1 It has been reported that the human ALAS2 gene is mapped on the X chromosome, 2 and that a loss-of-function mutation of this gene causes X-linked sideroblastic anemia (XLSA), 3,4 which is the most common genetic form of congenital sideroblastic anemia (CSA). Moreover, a missense mutation of ALAS2 was identified in a patient with non-familial CSA (nfCSA), 5 in which no family history of sideroblastic anemia was identified.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been reported that the human ALAS2 gene is mapped on the X chromosome, 2 and that a loss-of-function mutation of this gene causes X-linked sideroblastic anemia (XLSA), 3,4 which is the most common genetic form of congenital sideroblastic anemia (CSA). Moreover, a missense mutation of ALAS2 was identified in a patient with non-familial CSA (nfCSA), 5 in which no family history of sideroblastic anemia was identified.…”
Section: Introductionmentioning
confidence: 99%
“…In congenital sideroblastic anemia (CSA), Hb and MCV are usually lower than those of refractory anemia with ring sideroblasts (RARS) and refractory cytopenia with multilineage dysplasia (RCMD) cases; serum iron level in CSA is also commonly higher than that in RARS or RCMD [1,2]. This together with the presence of family history and the young age of the patient and the presence in the blood smear of a dimorphic population of red blood cells and a normal karyotype led us to apply genetic study of deltaaminolevulinate synthase 2 (ALAS2) gene.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The three most common causes of microcytosis are iron deficiency, the anemia of (chronic) inflammation, and alpha or beta thalassemia trait [1]. However, less frequent causes such as sideroblastic anemias, hemoglobinopathies, lead poisoning and rare and atypical inherited microcytic anemias due to defects of iron metabolism should be taken into account [2].…”
Section: Introductionmentioning
confidence: 99%
“…Within these heme biosynthetic enzymes, the mutation of the ALAS2 gene is most frequently identified in patients with congenital sideroblastic anemia [49,50]. Since human ALAS2 gene is mapped to X chromosome [30,51], congenital sideroblastic anemia (CSA) caused by the mutation of ALAS2 gene exhibits X-linked inheritance pattern (X-linked sideroblastic anemia; XLSA).…”
Section: Heme Biosynthesis In Erythroid Cellsmentioning
confidence: 99%